Targeted Hyperparameter Optimization with Lexicographic Preferences Over Multiple Objectives - Zhang, Shaokun; Jia, Feiran; Wang, Chi; Wu, Qingyun (2023 International Conference on Learning Representations, 2023)
Motivated by various practical applications, we propose a novel and general formulation of targeted multi-objective hyperparameter optimization. Our formulation allows a clear specification of an automatable optimization goal using lexicographic preference over multiple objectives. We then propose a randomized directed search method named LexiFlow to solve this problem. We demonstrate the strong empirical performance of the proposed algorithm in multiple hyperparameter optimization tasks.